Goddesses in Religions and in Modern Debate - Bulley, Alan D (Journal of Dharma, 1993)
Goddesses in Religions and in Modern Debate. Larry Hurtado, ed. University of Manitoba Studies in Religion, 1 . Atlanta: Scholar's Press, 1 990.